A Novel Method to Estimate Height of an Individual with Facial Index - Arunashri; Lalitha C.; Venkateshu K.V. (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: Face is the most important part of the body. Cranial anthropometry is well known determinant ofgood and important aspects of treatment in the field of medicine, dentistry, plastic surgery, aesthetics. Thereare studies on the facial index determination and classification of faces. There are very few studies on theestimation of height of an individual from facial index as a parameter. Here in this study, we have aimed toestimate height of an individual from facial index derived from his/her 2D photograph. Therefore, here inthis study we have attempt to estimate height from the facial index of an individual.Materials and Methods: Study population were randomly selected 105 samples to measure the facialparameters using digital vernier calipers manually, and also height with the help of stadiometer. Then thefacial index was determined from the postcard size photograph of an individual, then classified based onBannister classification and formula was derived to estimate the height of an individual from it.Result and Conclusion: We observe a correlation existing between the facial index and the height of anindividual. This study will be of great utility for the forensic application for estimation of height from the2D photograph of an individual.